1997
DOI: 10.1177/174182679700400303
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Coronary Heart Disease in a Population with a High Prevalence of Obesity and Diabetes: A Case-Control Study of the Polynesian Population of Western Samoa

Abstract: Objective To evaluate anthropometric, haemodynamic and biochemical risk markers for coronary heart disease (CHD) in the Polynesian population of Western Samoa in a case-control study of 43 cases of CHD compared with 9 0 age-(mean 53 years) and sex-matched controls.Methods Cases were identified on the basis of a 1 2-lead electrocardiogram and clinical history. ResultsMore than 60% of the participants had a body mass index 230 kg/m2 and nearly 80% had central obesity. Both diabetes mellitus (1 7%) and impaired g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…To date, 17 cross-sectional epidemiologic [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], eight prospective epidemiologic [28-33,34••,35], and six clinical intervention trials [36][37][38][39][40][41] have examined the relationship of LDL particle size and CHD risk. Of the 17 cross-sectional studies reviewed, 12 demonstrated a significant univariate relationship between small-sized LDL particles and CHD [12][13][14][15][16][17][18][24][25][26][27], whereas two trials [19,20] reported an association of large-sized LDL particles with CHD.…”
Section: Relationship Of Low-density Lipoprotein Particle Size With Cmentioning
confidence: 99%
“…To date, 17 cross-sectional epidemiologic [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], eight prospective epidemiologic [28-33,34••,35], and six clinical intervention trials [36][37][38][39][40][41] have examined the relationship of LDL particle size and CHD risk. Of the 17 cross-sectional studies reviewed, 12 demonstrated a significant univariate relationship between small-sized LDL particles and CHD [12][13][14][15][16][17][18][24][25][26][27], whereas two trials [19,20] reported an association of large-sized LDL particles with CHD.…”
Section: Relationship Of Low-density Lipoprotein Particle Size With Cmentioning
confidence: 99%
“…15,16 Predominance of small LDL in patients with coronary disease may simply reflect these other traits, and so its clinical utility has been questioned. 16,17 Indeed, in studies in which triglyceride concentrations were similar in cases and controls, small LDL was either unrelated 9,10,14 or inversely related 7,8 with risk of coronary disease. Because of such strong confounding, the true direct relationship, if any, between LDL size and coronary disease has been difficult to determine.…”
mentioning
confidence: 93%
“…Although more recent studies have resulted in renewed attention to the relationship between quality of life and being overweight (6, 7, 8, 9, 10, 11, 12, 13), this research has generally been limited to special populations or to studies conducted outside the United States. Because the prevalence of overweight and obesity varies widely across cultures (14, 15, 16) and because the impact of obesity may, in part, be culturally determined, we used data from the 1996 Behavioral Risk Factor Surveillance Survey (BRFSS) to examine the association between health‐related quality of life and self‐reported body mass index (BMI) in a large sample of U.S. adults. We explored this relationship across age groups, among men and women, and among different racial or ethnic groups in the United States.…”
Section: Introductionmentioning
confidence: 99%